943Impact of maternal factors, pregnancy complications, and birth outcomes on the neonate metabolome. (2nd September 2021) - Mansell, Toby; Collier, Fiona; Ellul, Susan; Burgner, David; Saffery, Richard; ,
Abstract: Background: Metabolic health in early life is critical for healthy development and can have long-lasting ramifications of risk of disease into adulthood. While many exposures during pregnancy are linked to altered fetal development and/or risk of disease in adult offspring, the molecular mechanisms underpinning these associations are poorly characterised. We aimed to describe the association between pregnancy/birth exposures and neonate metabolomics profile. Methods: Metabolomics in cord blood plasma from 912 neonates in the Barwon Infant Study was quantified using the Nightingale Health NMR platform. Questionnaire and clinical data collected included maternal anthropometry, pregnancy complications, mode of delivery and infant anthropometry at birth. Linear regression models were used to investigate the relationship between these factors and 70 neonate metabolomics measures. Results: Infant sex, gestational age, birth weight, and exposure to labour during birth were associated with differences across a wide range of metabolites. Exposure to gestational diabetes was associated with increased ketone bodies (acetoacetate and 3-hydroxybutyrate), and this relationship persisted after adjustment for other maternal and pregnancy exposures including maternal BMI. Maternal BMI was modestly associated with increased neonate triglycerides and inflammation. Conclusions: Birth outcomes show compelling evidence for wide-spread differences in neonate metabolites in cord blood serum, and exposure to gestational diabetes is associated with increased ketone bodies. Further work is required to understand the biological processes underpinning these relationships and to determine if differences in metabolites persist later into childhood. Key messages: Sex, gestational age, birthweight and exposure to labour are linked to metabolomics differences in cord blood plasma. Gestational diabetes is associated with increased neonate ketone bodies.